Pioneering Women Lawyers Who Changed the Legal Profession and Influenced the Practice of Law, Including Mediation Practice: From Barkeloo and Couzins to the Present - Karen Tokarz (Washington University Journal of Law & Policy, 2020)
This Article considers the importance of the growth of women in the legal profession, specifically mediation as a form of legal dispute resolution. Using Professor Trina Grillo’s article, The Mediation Alternative: Process Dangers for Women, this Article focuses on the need for mindful mediation and reflective practice. Through a focus on voluntariness, self-determination, attention to bias, and attention to the process, a mediator may achieve a mindful and reflective practice.
Keywords: women; woman; legal profession; mediation; dispute resolution; legal dispute resolution; Trina Grillo; The Mediation Alternative: Process Dangers for Women